A SEMIO-PRAGMATIC ANALYSIS OF THE WORLD HEALTH ORGANIZATION’S CAMPAIGN POSTERS AGAINST COVID-19 - Mohammad Muhassin (Universitas Padjadjaran, 2022)
The Covid-19 pandemic has claimed hundreds of thousands of human lives in various parts of the world. As an authoritative body, the World Health Organization (henceforth WHO) has made efforts to prevent the Covid-19 outbreak by releasing appealing messages through posters. The study aims to to explore the types of linguistic elements used in the WHO posters and to uncover the meanings of the elements to express the messages. The study employed descriptive qualitative research using a semio-pragmatic analysis framework. The data were presented in the form of linguistic elements in posters themed #HealthyAtHome, taken from the World Health Organization’s official website. The study found two linguistic elements as poster-forming elements, namely visual and verbal elements. Through icons, indexes, and symbols, visual elements reinforce the meaning of the poster’s theme so that it is easily understood by readers. Meanwhile, verbal elements are realized by the directive speech to facilitate understanding of the intended message as well as indirective speech to consider politeness in delivering the messages. The implication of this study is to increase public knowledge and awareness on the best health practices that can be performed at home during the pandemic.